High Rate Magnesium–Sulfur Battery with Improved Cyclability Based on Metal–Organic Framework Derivative Carbon Host. Issue 7 (8th January 2018) - Zhou, Xuejun; Tian, Jing; Hu, Jiulin; Li, Chilin
Abstract: Mg batteries have the advantages of resource abundance, high volumetric energy density, and dendrite‐free plating/stripping of Mg anodes. However the injection of highly polar Mg 2+ cannot maintain the structural integrity of intercalation‐type cathodes even for open framework prototypes. The lack of high‐voltage electrolytes and sluggish Mg 2+ diffusion in lattices or through interfaces also limit the energy density of Mg batteries. Mg–S system based on moderate‐voltage conversion electrochemistry appears to be a promising solution to high‐energy Mg batteries. However, it still suffers from poor capacity and cycling performances so far. Here, a ZIF‐67 derivative carbon framework codoped by N and Co atoms is proposed as effective S host for highly reversible Mg–S batteries even under high rates. The discharge capacity is as high as ≈600 mA h g −1 at 1 C during the first cycle, and it is still preserved at ≈400 mA h g −1 after at least 200 cycles. Under a much higher rate of 5 C, a capacity of 300–400 mA h g −1 is still achievable. Such a superior performance is unprecedented among Mg–S systems and benefits from multiple factors, including heterogeneous doping, Li‐salt and Cl − addition, charge mode, and cut‐off capacity, as well as separator decoration, which enable the mitigation of electrode passivation and polysulfide loss. Abstract : A ZIF‐67 derivative carbon framework codoped by N and Co atoms is proposed as an effective S host for highly reversible Mg–S batteries even under high rate up to 5C. The discharge capacity is preserved at 450 mA h g −1 after 250 cycles for 0.1C and 400 mA h g −1 after 200 cycles for 1C. Such a superior performance also benefits from Li‐salt and Cl − addition, charge mode, capacity cut‐off, and separator decoration.